2022
DOI: 10.14309/01.ajg.0000861640.53682.93
|View full text |Cite
|
Sign up to set email alerts
|

S1250 A Pilot Study to Improve Resident Paracentesis Training and Reduce Paracentesis Delay in Admitted Patients With Cirrhosis

Abstract: We aimed to assess statin utilization as a function of calculated ASCVD risk score in HCV-infected individuals to further understand the implications of the inaccuracies with the Pooled Cohort Equation in estimating CVD risk in this population. Methods: We performed a single-center retrospective study of HCV-infected individuals aged 40-75 years. The 10-year ASCVD risk score was calculated for each subject using the 2013 American College of Cardiology/American Heart Association Pooled Cohort Equation. Statin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Pham and colleagues showed that integrating paracentesis into timely training can reduce paracentesis delay and delays in care. 7 By increasing the volume of procedures each resident performs and creating a sense of confidence amongst residents, the clinic increases the number of residents able and willing to perform inpatient procedures, thus reducing the number of unnecessary consultations and hospital resources. One of the reasons the paracentesis clinic was started was to allow patients to have scheduled times to remove fluid from their abdomen, thus cutting down on emergency depart-ment procedures and unnecessary admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Pham and colleagues showed that integrating paracentesis into timely training can reduce paracentesis delay and delays in care. 7 By increasing the volume of procedures each resident performs and creating a sense of confidence amongst residents, the clinic increases the number of residents able and willing to perform inpatient procedures, thus reducing the number of unnecessary consultations and hospital resources. One of the reasons the paracentesis clinic was started was to allow patients to have scheduled times to remove fluid from their abdomen, thus cutting down on emergency depart-ment procedures and unnecessary admissions.…”
Section: Discussionmentioning
confidence: 99%